UV photocuring hydrophobic antibacterial material for bathroom and preparation method thereof

By introducing photocurable thiol and vinyl groups into the bathroom materials, and using UV light to excite the click reaction, UV photocurable hydrophobic materials for bathrooms with high hardness, good adhesion and excellent hydrophobic antibacterial properties were prepared, which solved the problem of poor antibacterial effect of existing bathroom materials in humid environments, and achieved healthy, safe, economical and practical material preparation.

CN119570364APending Publication Date: 2025-03-07KAIPING YUFA SANITARY WARE CO LTD +1

Patent Information

Application Number
CN202411749895.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing bathroom materials are prone to bacterial growth in humid environments, have poor antibacterial effects, do not last long, and have high preparation costs, making it difficult to meet the needs of health, safety, economical and practicality.

Method used

By introducing photocurable thiol and vinyl groups into organozirconium nanoparticles, titanium dioxide nanoparticles and silicone resins, UV light curing is achieved, and hydrophobic antibacterial materials are prepared.

Benefits of technology

The prepared UV photocurable hydrophobic antibacterial material has extremely high hardness, good adhesion and excellent hydrophobic antibacterial properties. It is suitable for use in bathroom materials, which is convenient and fast to use and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164747410000041
    Figure BDA0005164747410000041
  • Figure BDA0005164747410000081
    Figure BDA0005164747410000081
Patent Text Reader

Abstract

The invention belongs to the field of bathroom materials, and discloses a UV photocuring hydrophobic antibacterial material as well as a preparation method and application thereof. The purpose of photocuring is achieved by introducing photocurable sulfydryl and vinyl into organic zirconium nanoparticles, titanium dioxide nanoparticles and organic silicon resin: the sulfydryl and vinyl are subjected to click reaction under the irradiation of ultraviolet light, so that the photocuring is rapid, the photocuring is not afraid of oxygen inhibition, the curing can be carried out in the air, and the use is more convenient and rapid. The introduction of the organic zirconium nanoparticles improves the hardness of the material, the introduction of the zwitterion modified titanium dioxide nanoparticles endows the material with antibacterial property, the introduction of the organic silicon resin improves the hydrophobic property of the material, and the prepared photocuring material has extremely high hardness, good adhesion and excellent hydrophobic and antibacterial properties. The hydrophobic antibacterial material is especially suitable for bathrooms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sanitary materials, and in particular relates to a UV light-cured hydrophobic antibacterial material and a preparation method thereof. Technical Background

[0002] As people pursue a better quality of life, bathroom products are constantly being upgraded, and health and intelligence have become the direction of product development. What needs attention is that there are many sources of microbial contamination in the bathroom space. Bathtubs / tubs and showers have water flowing all year round, and the warm and humid environment provides a breeding ground for bacteria. If the cleaning work is not in place, it is easy to breed a large number of bacteria. Therefore, the antibacterial issue has become an important concern for bathroom products. It is of great significance to prepare materials with high efficiency, broad spectrum, health, safety, long-term effect and high stability for bathroom products.

[0003] Bathroom products are products that consumers use every day, but due to the humid environment, bathroom products are prone to bacteria, which is not good for human health. Although there are some bathroom materials that claim to have bactericidal functions, their antibacterial effects are poor and do not last long. At the same time, the preparation cost is high, which is not conducive to promotion and use.

[0004] Patent document CN106673633A discloses an antibacterial sanitary ceramic product and a preparation method thereof, including a body and a glaze, wherein the raw materials of the glaze contain titanium dioxide and nano-silver that can kill bacteria. The raw materials of the body are crushed, wet ball milled, left to age, slip cast, demolded, dried, and bisque fired to obtain a body; then the glaze is wet ball milled, left to age, and then sprayed on the surface of the body to obtain a product to be fired, and then glaze fired to obtain an antibacterial sanitary ceramic product. The antibacterial sanitary ceramic product prepared by the invention has good weather resistance, antibacterial properties, and low water absorption, but the method is only applicable to the preparation of ceramic materials. Patent CN116446013 invented a method for preparing a wear-resistant antibacterial coating for bathroom hardware. By preparing a composite material of metal organic framework material coated with metal particles, an electrochemical deposition reaction is used to form a wear-resistant antibacterial coating on the surface of the bathroom hardware substrate. The coating prepared by the invention not only has excellent antibacterial and self-cleaning properties, but also has a strong bond with the substrate, which can meet the long-term use requirements of bathroom hardware under harsh conditions. However, the only drawback is that this method uses electrochemical deposition reaction, which is only useful for metal substrates and will not be suitable for some non-conductive bathroom products. However, its method for preparing antibacterial coatings on the surface of materials provides a reference idea. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing a UV light-curable hydrophobic antibacterial material for bathrooms. The UV light-curable hydrophobic antibacterial material for bathrooms achieves the purpose of photocuring by introducing photocurable thiol and vinyl groups into organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resins: the thiol and vinyl groups undergo a click reaction under the irradiation of ultraviolet light, and the photocuring is rapid, not afraid of oxygen inhibition, and can be cured in the air, which is more convenient and quick to use.

[0006] Another object of the present invention is to provide organic zirconium nanoparticles, organic titanium nanoparticles and organic silicon resin prepared by the above method.

[0007] Another object of the present invention is to provide an application of UV light-cured hydrophobic antibacterial material. The introduction of organic zirconium nanoparticles improves the hardness of the material, the introduction of zwitterion-modified titanium dioxide nanoparticles provides the antibacterial property of the material, and the introduction of organic silicone resin improves the hydrophobic property of the material. The prepared light-cured material has extremely high hardness, good adhesion and excellent hydrophobic antibacterial property, and is particularly suitable for use as a bathroom material.

[0008] The purpose of the present invention is achieved through the following solutions:

[0009] A method for preparing a UV light-curing hydrophobic material for bathrooms comprises the following steps: firstly, alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane are subjected to hydrolysis and condensation to prepare organic zirconium nanoparticles modified with mercapto and long-chain alkyl groups; secondly, alkyl titanate, zwitterionic silane and mercaptosilane are subjected to hydrolysis and condensation to prepare titanium dioxide nanoparticles modified with mercapto and zwitterionic groups; thirdly, alkyl silane and vinyl silane are subjected to hydrolysis and condensation to prepare organic silicone resin. Then, the prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and organic silicone resin are uniformly mixed with a small amount of solvent and then light-cured under UV light irradiation.

[0010] Preferably, the mercapto- and long-chain alkyl-modified organic zirconium nanoparticles are prepared by the following method: alkyl zirconium alcohol, mercaptosilane, long-chain alkyl silane, catalyst and solvent are uniformly mixed, the temperature is increased for hydrolysis and condensation, and after a period of reaction, the solvent is removed by rotary evaporation to obtain mercapto- and long-chain alkyl-modified organic zirconium nanoparticles.

[0011] Preferably, the mercapto and zwitterion modified titanium dioxide nanoparticles are prepared by the following method: alkyl titanate, mercaptosilane, zwitterion silane, catalyst and solvent are uniformly mixed, the temperature is increased for hydrolysis and condensation, and after a period of reaction, the solvent is removed by rotary evaporation to obtain mercapto and zwitterion modified titanium dioxide nanoparticles.

[0012] Preferably, the organosilicon resin is prepared by the following method: alkyl silane, vinyl silane, catalyst and solvent are uniformly mixed, the mixture is heated to carry out hydrolysis and condensation, and after a period of reaction, the solvent is removed by rotary evaporation to obtain the organosilicon resin.

[0013] The zirconium alkyl alcohol is one of zirconium ethoxide, zirconium n-propoxide, zirconium n-butoxide or zirconium tert-butoxide.

[0014] The mercaptosilane is one of (3-mercaptopropyl)trimethoxysilane and (3-mercaptopropyl)triethoxysilane.

[0015] The long-chain alkyl silane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and octadecyltriethoxysilane.

[0016] The catalyst is at least one of acetic acid and dilute hydrochloric acid.

[0017] The solvent is at least one of ethanol and isopropanol.

[0018] The heating for hydrolysis condensation means raising the temperature to 40-60° C. for reaction for 4-8 hours; preferably, raising the temperature to 50° C. for reaction for 6 hours.

[0019] The amounts of the alkyl zirconium alcohol, mercaptosilane, long-chain alkyl silane, catalyst and solvent meet the following requirements: the molar ratio of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane.

[0020] The alkyl titanate is one of tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.

[0021] The mercaptosilane is one of (3-mercaptopropyl)trimethoxysilane and (3-mercaptopropyl)triethoxysilane.

[0022] The zwitterionic silane is sulfobetaine silane.

[0023] The catalyst is at least one of acetic acid and dilute hydrochloric acid.

[0024] The solvent is at least one of ethanol and isopropanol.

[0025] The heating for hydrolysis condensation means raising the temperature to 40-60° C. for reaction for 4-8 hours; preferably, raising the temperature to 50° C. for reaction for 6 hours.

[0026] The amounts of the alkyl titanate, mercaptosilane, zwitterionic silane, catalyst and solvent are as follows: the molar ratio of the alkyl titanate, mercaptosilane and zwitterionic silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl titanate, mercaptosilane and zwitterionic silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl titanate, mercaptosilane and zwitterionic silane.

[0027] The alkylsilane is one of 1,2-bis(trimethoxysilyl)ethane and 1,6-bis(trimethoxysilyl)hexane.

[0028] The vinyl silane is one of triethoxyvinyl silane, diethoxymethylvinyl silane, trimethoxyvinyl silane, dimethoxymethylvinyl silane, allyltrimethoxysilane and allyltriethoxysilane.

[0029] The catalyst is at least one of acetic acid and dilute hydrochloric acid.

[0030] The solvent is at least one of ethanol and isopropanol.

[0031] The heating for hydrolysis condensation means raising the temperature to 40-60° C. for reaction for 4-8 hours; preferably, raising the temperature to 50° C. for reaction for 6 hours.

[0032] A UV light-curing hydrophobic material for bathroom use prepared by the method.

[0033] Preferably, the structural formula of the UV light-curable hydrophobic material for bathroom use is specifically as follows:

[0034]

[0035] Where R 1 is a long chain alkyl group, R 2 is a thiol group, R 3 For zwitterions, R 4 is a thiol group, R 5 is an alkyl group, R 6 For vinyl.

[0036] The above-mentioned UV light-curing hydrophobic antibacterial material for bathroom is dissolved by adding a small amount of solvent in a certain proportion, and then adding a small amount of photoinitiator and stirring evenly, and then applied to bathroom surfaces such as metal, glass, ceramic or plastic. After a short period of UV light exposure (such as 5s) in the air, it can be completely dry on the surface. The cured material has good hydrophobicity, antibacterial, heat resistance and transparency, as well as good adhesion, high hardness, and good wear resistance, and is widely used in bathroom materials.

[0037] The certain proportion refers to the addition of organic zirconium nanoparticles, titanium dioxide nanoparticles and organic silicone resin in a substance amount ratio of 1:1:1.7 to 2.3.

[0038] The photoinitiator refers to a compound that can generate free radicals under ultraviolet light irradiation, and is at least one of 2-hydroxy-2-methylpropiophenone (Darocur1173), 1-hydroxy-cyclohexyl benzophenone (Darocur184), 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide (TEPO) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO); the added amount of the photoinitiator is 1% to 4% of the total mass of the organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin.

[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] The hydrophobic sterilizing material for bathroom prepared by the present invention has a simple preparation method. The thiol group and double bond capable of photocuring are simultaneously introduced into the organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin. The material is not afraid of oxygen inhibition and can be UV-cured in the air, making it more convenient and quick to use. At the same time, the zwitterionic structure is introduced into the titanium dioxide nanoparticles to enhance the antibacterial property of the titanium dioxide nanoparticles. The UV-cured material has excellent hydrophobicity, sterilization, heat resistance, transparency, adhesion and hardness, and is widely used in the field of bathrooms. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The sulfobetaine silane used in the present invention is homemade, and the preparation method is as follows: (N,N-dimethylaminopropyl)trimethoxysilane and 1,3-propane sultone are added to a reaction vessel, the molar ratio of the two is 1:1.2, an appropriate amount of acetone is added to dissolve, and after stirring at room temperature for 6 hours under nitrogen protection, the mixture is washed and filtered with acetone, and a white solid is obtained after vacuum drying. Other raw materials or instruments involved in the present invention can be purchased directly from the market. For process parameters not specifically noted, conventional techniques can be referred to.

[0042] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0043] Example 1

[0044] Zirconium n-propoxide, (3-mercaptopropyl)trimethoxysilane, dodecyltrimethoxysilane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups.

[0045] Tetraethyl titanate, (3-mercaptopropyl)trimethoxysilane, sulfobetaine silane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain mercapto and zwitterion-modified titanium dioxide nanoparticles.

[0046] 1,2-bistrimethoxysilylethane and triethoxyvinylsilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.

[0047] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0048] Example 2

[0049] Zirconium n-butoxide, (3-mercaptopropyl)triethoxysilane, dodecyltriethoxysilane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups.

[0050] The preparation of titanium dioxide nanoparticles and silicone resin is as in Example 1.

[0051] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0052] Example 3

[0053] The preparation of organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.

[0054] Tetraethyl titanate, (3-mercaptopropyl)triethoxysilane, sulfobetaine silane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain mercapto and zwitterion-modified titanium dioxide nanoparticles.

[0055] The preparation of the silicone resin is as in Example 1.

[0056] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0057] Example 4

[0058] The preparation of organic zirconium nanoparticles and titanium dioxide nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.

[0059] 1,6-bis(trimethoxysilyl)hexane, triethoxyvinylsilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.

[0060] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0061] Example 5

[0062] The preparation of organic zirconium nanoparticles and titanium dioxide nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.

[0063] 1,2-bis(trimethoxysilyl)ethane and trimethoxyvinylsilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.

[0064] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0065] Example 6

[0066] The preparation of organic zirconium nanoparticles and titanium dioxide nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.

[0067] 1,6-bis(trimethoxysilyl)hexane and trimethoxyvinylsilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.

[0068] The prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin were mixed evenly with ethyl acetate, 1% of photoinitiator 1173 and TPO were added, and the mixture was coated with a wire rod to form a film. After irradiation with ultraviolet light for 5 seconds, a photocured hydrophobic antibacterial material was obtained.

[0069] The properties of the UV-cured hydrophobic antibacterial materials in the above examples are shown in the following table.

[0070] Table 1. UV curing hydrophobic antibacterial material properties of the examples

[0071]

[0072] in:

[0073] UV curing time refers to the irradiation time of a 2 kW high pressure mercury lamp commonly used in the market. The radiation energy in 5 seconds is 300 mj / cm 2 ;

[0074] The hydrophobic angle is the contact angle measured by a commercially available contact angle meter using water as the liquid. A hydrophobic angle greater than 90° indicates good hydrophobicity.

[0075] Heat resistance is the data obtained by measuring the weight loss relationship of the cured film using Mettler's thermal analyzer (Mettler TGA / DSC). The test conditions are nitrogen atmosphere, heating from 30°C to 800°C, and the heating rate is 10°C / min. Here T 5% Indicates the temperature at which the cured film loses 5% of its weight, T max Indicates the temperature at which the weight loss rate of the cured film is the maximum;

[0076] Transparency is the transmittance of a cured film with a thickness of 20 microns measured by ultraviolet spectroscopy. The test instrument is Shimadzu's UV-2600, and the test wavelength is 400-800nm ​​(visible light wavelength range);

[0077] The adhesion test is based on the cross-cut method of GB / T 9286-2021, with 0 being the best and 5 being the worst;

[0078] The hardness test is based on the pencil hardness method of GB / T 6739-2022, 9B means the softest and 9H means the hardest;

[0079] The antibacterial test is based on the surface antibacterial activity of GB / T 31402-2023. When the antibacterial rate is 100%, it means the best bactericidal performance.

[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a UV light-cured hydrophobic antibacterial material for bathroom use, characterized in that: The following steps are involved: The UV light-curable hydrophobic material is obtained by introducing photocurable mercapto groups and vinyl groups into organic zirconium nanoparticles, titanium dioxide nanoparticles and organic silicone resin.

2. The method for preparing a UV light-curing hydrophobic antibacterial material for bathroom use according to claim 1, characterized in that: The following steps are involved: Firstly, alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane are hydrolyzed and condensed to prepare mercapto- and long-chain alkyl-modified organic zirconium nanoparticles; secondly, alkyl titanate, zwitterionic silane and mercaptosilane are hydrolyzed and condensed to prepare mercapto- and zwitterionic-modified titanium dioxide nanoparticles; finally, alkyl silane and vinyl silane are hydrolyzed and condensed to prepare silicone resin, and then the prepared organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin are evenly mixed with a small amount of solvent and then photocured under UV light.

3. The method for preparing a UV light-curing hydrophobic antibacterial material for bathroom use according to claim 2, characterized in that: The organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups are prepared by the following method: alkyl zirconium alcohol, mercaptosilane, long-chain alkylsilane, catalyst and solvent are uniformly mixed, and then heated for hydrolysis and condensation. After a period of reaction, the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups; The mercapto and zwitterion modified titanium dioxide nanoparticles are prepared by the following method: alkyl titanate, mercaptosilane, zwitterion silane, catalyst and solvent are uniformly mixed, the temperature is increased for hydrolysis and condensation, after a period of reaction, the solvent is removed by rotary evaporation to obtain mercapto and zwitterion modified titanium dioxide nanoparticles; The organic silicone resin is specifically prepared by the following method: after uniformly mixing alkyl silane, vinyl silane, a catalyst and a solvent, heating the mixture for hydrolysis and condensation, after a period of reaction, removing the solvent by rotary evaporation to obtain the organic silicone resin.

4. The method for preparing a UV light-curing hydrophobic antibacterial material for bathroom use according to claim 3, characterized in that: The zirconium alkyl alcohol is zirconium ethanol, zirconium n-propoxide, zirconium n-butoxide or zirconium tert-butoxide; The mercaptosilane is trimethoxysilane or triethoxysilane; The long-chain alkyl silane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and octadecyltriethoxysilane; The catalyst is at least one of acetic acid and dilute hydrochloric acid; The solvent is at least one of ethanol and isopropanol; Heating for hydrolysis condensation means raising the temperature to 40-60°C for 4-8 hours; The amounts of the alkyl zirconium alcohol, mercaptosilane, alkyl silane, catalyst and solvent meet the following requirements: the molar ratio of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane.

5. The method for preparing a UV light-curing hydrophobic antibacterial material for bathroom use according to claim 3, characterized in that: The alkyl titanate is one of tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate; The mercaptosilane is trimethoxysilane or triethoxysilane; The zwitterionic silane is sulfobetaine silane; The catalyst is at least one of acetic acid and dilute hydrochloric acid; The solvent is at least one of ethanol and isopropanol; Heating the temperature for hydrolysis condensation means raising the temperature to 40-60°C and reacting for 4-8 hours. The amounts of the alkyl titanate, mercaptosilane, zwitterionic silane, catalyst and solvent are as follows: the molar ratio of the alkyl titanate, mercaptosilane and zwitterionic silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl titanate, mercaptosilane and zwitterionic silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl titanate, mercaptosilane and zwitterionic silane.

6. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 3, characterized in that: The alkylsilane is one of 1,2-bis-ethane and 1,6-bis-hexane; The vinyl silane is one of triethoxyvinyl silane, diethoxymethylvinyl silane, trimethoxyvinyl silane, dimethoxymethylvinyl silane, allyltrimethoxysilane and allyltriethoxysilane; The catalyst is at least one of acetic acid and dilute hydrochloric acid; The solvent is at least one of ethanol and isopropanol; Heating the temperature for hydrolysis condensation means raising the temperature to 40-60°C and reacting for 4-8 hours.

7. A UV light-cured hydrophobic antibacterial material for bathroom use, characterized in that: The method for preparing a UV light-curing hydrophobic material for bathroom use as described in any one of claims 1 to 6 is used for preparation.

8. The UV light-curing hydrophobic antibacterial material for bathroom use according to claim 7, characterized in that The UV light-curable hydrophobic antibacterial material is mixed and a photoinitiator needs to be added for UV curing.

9. The UV light-curing hydrophobic antibacterial material for bathroom use according to claim 7, characterized in that: The mixing of the UV light-curing hydrophobic antibacterial material refers to adding organic zirconium nanoparticles, titanium dioxide nanoparticles and organic silicone resin in a ratio of 1:1:1.7 to 2.

3.

10. The UV light-curing hydrophobic antibacterial material for bathroom use according to claim 7, characterized in that: The photoinitiator refers to a compound that can generate free radicals under ultraviolet light irradiation, and is at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the added amount of the photoinitiator is 1% to 4% of the total mass of the organic zirconium nanoparticles, titanium dioxide nanoparticles and silicone resin.

Citation Information

Patent Citations

  • Antibacterial bathroom ceramic article and preparation method thereof

    CN106673633A

  • Preparation method and application of nano zirconium-titanium composite sol / organosilicon modified hybrid resin

    CN104725643A

  • Composition having siloxane polymer and particle

    CN106612617A

  • Transparent super-hydrophilic antifogging coating based on zwitter-ions and preparation method of transparent super-hydrophilic antifogging coating

    CN118063829A

  • External facing material for construction and coating liquid for building exterior

    JP2011058273A

Cited By

  • Mirror-polished thin ceramic rock plate and preparation method thereof

    CN121554307A

  • Mirror-polished thin ceramic rock plate and preparation method thereof

    CN121554307B